The Patient Teacher in General Practice Training: Perspectives of Residents. (December 2019) - Aires, Marie José; Gagnayre, Rémi; Gross, Olivia; Khau, Cam-Anh; Haghighi, Sophie; Mercier, Alain; Ruelle, Yannick; Marchand, Claire
Background: Patient teachers were involved in training general practice residents (GPRs) to strengthen the patient-centered approach. They teach a course on health democracy by themselves and teach in tandem with a physician teacher during reflective practice-based classes (named GEPRIs). We present the GPRs' representations of patient teacher characteristics and capacities and their perception of how useful patient teachers are to their professional development. Methods: We administered a questionnaire based on a preliminary qualitative study to 124 GPRs. It explored (a) changes in the GPRs' representations about patient teacher characteristics and capacities with regard to teaching over the first year of the experiment; (b) GPRs' perception of patient teacher utility to their training and their contribution to developing patient perspective–related competencies. Results: The response rate was 89.5% (111/124). The majority of GPRs agreed with 17 (before) and 21 (after) of the 23 patient teacher characteristics and with 17 (before) and 19 (after) of the 20 capacities. The agreement rate increased, overall, after patient teacher participation. The GPRs found patient teacher useful to their training in 9 of 11 topics (agreement rate 65%-92%). They felt they had developed the 14 patient knowledge–related competencies (agreement rate 62%-93%), and 52% to 75% of the GPRs rated the patient teachers' contribution to those competencies "high or very high, " depending on the competency. Conclusion: This study demonstrates the specific contribution of patient teachers to university-level medical training in France. The GPRs recognized that patient teachers helped them develop competencies by providing patient-specific content.